Ultrastructural GABA immunogold labeling in the substantia nigra pars reticulata of kindled genetic absence epilepsy rats - AKAKIN, DİLEK; ONAT, FİLİZ; KAYA, ÖZLEM TUĞÇE; ŞİRVANCI, SERAP; KARAMAHMUTOĞLU, TUĞBA (TAYLOR & FRANCIS INC, 2020)
Genetic Absence Epilepsy Rats from Strasbourg (GAERS) is a well-known animal model of absence epilepsy and they are resistant to electrical kindling stimulations. The present study aimed to examine possible differences in gamma-aminobutyric acid (GABA) levels and synapse counts in the substantia nigra pars reticulata anterior (SNRa) and posterior (SNRp) regions between GAERS and Wistar rats receiving kindling stimulations. Animals in the kindling group either received six stimulations in the amygdala and had grade 2 seizures or they were kindled, having grade five seizures. Rats were decapitated one hour after the last stimulation. SNR regions were obtained after vibratome sectioning of the brain tissue. GABA immunoreactivity was detected by immunogold method and synapses were counted. Sections were observed by transmission electron microscope and analyzed by Image J program. GABA density in the SNRa region of fully kindled GAERS and Wistar groups increased significantly compared to that of their corresponding grade 2 groups. The number of synapses increased significantly in kindled and grade 2 GAERS groups, compared to kindled and grade 2 Wistar groups, respectively, in the SNRa region. GABA density in the SNRp region of kindled GAERS group increased significantly compared to that of GAERS grade 2 group. In the SNRp region, both kindled and grade 2 GAERS groups were found to have increased number of synapses compared to that of GAERS control group. We concluded that both SNRa and SNRp regions may be important in modulating resistance of GAERS to kindling stimulations.
Keywords: GAERS; kindling; electron microscopy; immunocytochemistry; GABAERGIC CELL-LINE; INTRANIGRAL TRANSPLANTS; ELECTRICAL-STIMULATION; SEIZURE SUPPRESSION; RESISTANCE; MODEL; INACTIVATION; MECHANISMS; NEURONS